DIVERSITE DE LA FAUNE VERTEBREE DU BARRAGE FOUM EL GHERZA (BISKRA, ALGERIE) - BRAHIMI, AMINA; BELHAMRA, MOHAMED (Courrier du Savoir; Vol. 21 (2016): COURRIER DU SAVOIR (NOVEMBRE), 2016)
The downstream of the Abiod River to level of Foum-El-Gherza dam constitutes a wetland which remains of water during all the year. It corresponds to a model site on which the regular surveys get interesting results of specific vertebrate fauna to prepare a plan of interpretation to the conservation and the management of this natural heritage. Forty six vertebrates’ species belonging to 31 families and 41 genera are observed in the site, with 7 fish species, 3 amphibians, 9 reptiles, 20 waterbirds and 7 mammals. The lake of dam shelters an endemic fish species of the Algerian Sahara: the Biskra’ Barbel (Luciobarbus biscarensis). For the waterbirds, the lake constitutes a part of a migratory halt, a place of wintering and a site of nesting. Two mammals protected in Algeria were observed: the Barbary ground squirrel (Atlantoxerus getulus) and Gundi (Ctenodactylus gundi). Also, five reptiles protected are noted: the Egyptian Cobra (Naja haje), the Bell's dabb lizard (Uromastix acanthinura), the Large Psammodromus (Psammodromus algirus), the Sandfish (Scincus scincus) and the Common Chameleon (Chamaeleo chamaeleon).